TACIT KNOWLEDGE MANAGEMENT AND PRESERVATION IN ORGANIZATIONS: A SYSTEMATIC LITERATURE REVIEW - Henry Sandika; Muhamad Prabu Wibowo; Tamara Adriani Salim (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2026)
Tacit knowledge is a strategic organizational asset in the form of individual experience, expertise, and intuition that is difficult to manage due to its implicit and contextual nature. Previous studies have extensively explored knowledge management practices, but limited attention has been paid to understanding the preservation of tacit knowledge within organizations. This article aims to systematically identify the forms of tacit knowledge managed by organizations, their preservation mechanisms, and the challenges organizations face in implementing such management and preservation. The research method used was a Systematic Literature Review (SLR), which examined reputable scientific articles relevant to the theme of tacit knowledge management and preservation in organizations. The PRISMA method was used to select articles, resulting in 33 articles relevant to the research objectives. The results indicate that tacit knowledge in organizations generally takes the form of practical experience, individual insights, technical skills, and community insights. Management and preservation are carried out through informal sharing mechanisms, mentoring, formal training, the use of technology, and Communities of Practice (CoP). However, the management and preservation of tacit knowledge face various challenges, particularly related to a lack of organizational support, a lack of trust between individuals, difficulties in standardization, ineffective use of technology, rigid bureaucracies, and limited organizational resources. This study offers novelty by integrating forms of tacit knowledge, preservation mechanisms, and organizational challenges into a unified analytical framework, highlighting the importance of a socio-technical approach to maintaining organizational memory. The results provide theoretical contributions to advancing knowledge management literature, as well as practical implications for organizations in designing adaptive strategies to preserve strategic intellectual assets in dynamic environments.